Car Temperature Sensor - Abd Rashid, Nor Hafiza; Khaizurat, Shalmatun Shakhiyah (2016)
The Car Temperature Sensor with LCD display are design to detect a temperature surrounding environment with sensor LM35 and control the temperature . The main processing unit on devices is the PIC16F873. This project is using sensor LM35 as a sensor to measure the temperature. The LM35 Series are precision integrated-circuit temperature sensor, whose output voltage is linearly proportional to the Celsius (Centigrade) temperature. It does not require any external calibration or trimming to provide typical accuracies of ±0.25°C at room temperature and ±0.75°C and a lull -55°C to +150°C temperature range. But in this project, we used LM35 as the sensor to detect temperature. This type of sensor will measures the temperature in range 0°C to +100°C. It use Programmed Integrated Circuit (PIC) as a main component to process all the data by converting voltage receive from those sensors into its input, then convert it into the series of output to play the value of temperature and by connecting LCD (liquid Crystal Display).